1999
DOI: 10.1152/ajpregu.1999.276.1.r237
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of arginase isoforms I and II by IL-4 in cultured murine peritoneal macrophages

Abstract: Macrophages can express two arginase isoforms with distinct subcellular localization (cytosolic AI and mitochondrial AII). These isoforms are products of different genes and are capable of differential induction. Experiments were performed to identify the specific arginase isoforms induced by interleukin (IL)-4, a Th2 cytokine shown by others to increase arginase activity in macrophages, and serum. Results indicate IL-4, in concert with serum, increases AI, but not AII, mRNA in cultured murine macrophages. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
71
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 34 publications
9
71
0
2
Order By: Relevance
“…First, arginase up-regulation might rely on systemic inflammation and increased proinflammatory cytokines. Indeed, previous data demonstrated that arginase expression in cultured endothelial cells can be regulated by various proinflammatory cytokines or by lipopolysaccharide (41)(42)(43). In our study, in accordance with a systemic state of inflammation in AIA rats 21 days after the onset of arthritis, plasma levels of IL-6 increased by 62% in AIA rats compared with controls.…”
Section: Discussionsupporting
confidence: 88%
“…First, arginase up-regulation might rely on systemic inflammation and increased proinflammatory cytokines. Indeed, previous data demonstrated that arginase expression in cultured endothelial cells can be regulated by various proinflammatory cytokines or by lipopolysaccharide (41)(42)(43). In our study, in accordance with a systemic state of inflammation in AIA rats 21 days after the onset of arthritis, plasma levels of IL-6 increased by 62% in AIA rats compared with controls.…”
Section: Discussionsupporting
confidence: 88%
“…Whereas CAT-1, CAT-2B, and CAT-3 are high affinity (K M 100 mol/L) transporters for L-arginine, CAT-2A is an alternatively spliced variant of CAT-2B that possesses low affinity for L-arginine (K M 1 to 2 mmol/L) (32). In accordance with Louis et al (10), our data show that PM stimulated with IL-4 ϩ IL-13 up-regulate the expression of CAT-2B, displaying a similar kinetics to ASE I (Figs. 1C and 6B).…”
Section: Discussionsupporting
confidence: 79%
“…Stimulation of murine macrophages with IFN-␥ up-regulates iNOS exclusively, whereas IL-4, IL-10 and IL-13 induce ASE I (8,9). The mitochondrial isoform ASE II is not significantly modulated by Th1 or Th2 cytokines (7,10). …”
mentioning
confidence: 99%
“…Our previous study supports this contention, because inhibition of arginase activity enhances NO production from LPS-activated macrophages (26). Recently, arginase activity has been shown to be up-regulated by endogenous factors such as TGF-␤ (21) and Th-2 cell-derived cytokines IL-4 and IL-10 (22)(23)(24)(25). Interestingly, these factors were also reported to suppress NO production (21,22,41), implying that arginase might be an intrinsic modulator of NO production.…”
Section: Discussionsupporting
confidence: 69%